Mental Toughness Pada Atlet: Crosscheck Berdasarkan Gender dan Cabang Olahraga - Nasya Afriyani Aura Shaqina; Jajat; Syam Hardwis (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze differences in athletes' mental toughness based on gender and sports characteristics. The study used a quantitative approach with a comparative design. The participants consisted of 230 athletes from various sports with the characteristics of Game Sports, Accuracy, and Martial Arts. The instrument used was the Indonesian version of the SMTQ, consisting of 14 items across three dimensions: confidence, constancy, and control. Data were analyzed using the Mann-Whitney U Test and differences based on sports characteristics were analyzed using the Kruskal-Wallis test; all data processing was carried out using IBM SPSS Statistics 26 software. The results showed that: (1) there were significant differences based on gender in the confidence and control dimensions and in the total mental toughness score, with male athletes obtaining higher scores of 124.93 (confidence), 126.95 (control), and 124.98 (mental toughness score); (2) no significant difference was found in the constancy dimension based on gender; (3) based on sport characteristics, significant differences were found in the constancy dimension and total mental toughness score, with martial arts athletes showing higher scores than accuracy and game-sport athletes; and (4) the confidence and control dimensions did not show significant differences based on sport characteristics. Although the differences were statistically significant, the small effect sizes indicate that the contribution of gender and sport characteristics to the variation in mental toughness is relatively limited. Keywords: Athletes, Gender, Mental Toughness, Sport Characteristics, Sport Psychology